The profitability of wheat production in Ethiopia: The case of Tiyo Woreda in Arsi zone - Gavian, S.; Degefa, G. (1996)
The profitability of different wheat production systems in Arsi Zone was investigated by comparing farmers' practices in the 1994 crop season with on-farm demonstrations led by both Sasakawa-Global 2000 and Kulumsa Research Center of the Institute of Agriculture Research. Overall, yields on the demonstration plots were higher than those on unsupervised farmers' plots; while farmers do plant improved wheat varieties, they tend to recycle seeds retained from their own stock rather than purchasing new seeds each year. Additionally, they use far less fertilizer and herbicide than either MOA extension agents; or researchers' recommendations. A breakdown of farmer practices by the amount of purchased inputs shows that the top 4 percent of the farmers surveyed were able to produce as much or more grain on their fields as on the demonstration plots with comparable or greater profits. On the whole, however, the demonstration plots offer yields and profits greater than those most wheat farmers in this region are achieving, even after adjusting for capital costs and possible price fluctuations. The results of the economic analyses suggest the need for broader testing of the experimental packages. At the same time, the inability of many farmers to adopt existing high-input packages indicates the need to decrease the costs and the difficulty of obtaining purchased inputs. Furthermore, the study pointed out an apparent deficiency in the research/extension package: high-cost herbicides must be targeted for wheat fields having weed densities greater than some economic threshold levels.